ANALISIS KADAR KARBOHIDRAT PADA BIJI TUMBUHAN PAKIS HAJI (Cycas rumphii Miq) - John Elton Ngarbingan (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: Food is one of the basic needs needed by the body every day in certain amounts as a source of energy and nutrients. In the body, food substances containing carbon elements can be used as energy-forming materials, one of which is carbohydrates obtained from various food sources. Pakis haji (Cycas rumphii Miq) is one type of Pakis haji (Cycas) commonly found in the archipelago that grows on different substrates. In Maluku people know Pakis Haji with the title of